2020
DOI: 10.2478/jaiscr-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Parallel Implementation of Non-Iteratively Trained Recurrent Neural Networks

Abstract: Recurrent neural networks (RNN) have been successfully applied to various sequential decision-making tasks, natural language processing applications, and time-series predictions. Such networks are usually trained through back-propagation through time (BPTT) which is prohibitively expensive, especially when the length of the time dependencies and the number of hidden neurons increase. To reduce the training time, extreme learning machines (ELMs) have been recently applied to RNN training, reaching a 99% speedup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The results showed that COV-ELM outperforms new-generation machine learning algorithms. In El Zini et al [143], an ELM-based recurrent neural network training algorithm was presented that takes advantage of GPU-shared memory and parallel QR factorization algorithms to reach optimal solutions efficiently. The proposed algorithm reaches up to 461 times the speedup of its sequential counterpart.…”
Section: Graphics Processing Unitmentioning
confidence: 99%
“…The results showed that COV-ELM outperforms new-generation machine learning algorithms. In El Zini et al [143], an ELM-based recurrent neural network training algorithm was presented that takes advantage of GPU-shared memory and parallel QR factorization algorithms to reach optimal solutions efficiently. The proposed algorithm reaches up to 461 times the speedup of its sequential counterpart.…”
Section: Graphics Processing Unitmentioning
confidence: 99%
“…Each thread can either buffer or reveal its state. While speculative parallelism can be used for improving the performance of automatic parallelization algorithms, 59 it requires additional hardware or software support resulting additional overheads. Attempts are made to demonstrate a computationally efficient architectural framework to reduce the noncompulsory overhead associated with misspeculation.…”
Section: Related Workmentioning
confidence: 99%
“…However, this work is for the batch ELM algorithm and again it does not involve any regularization to prevent over‐fitting and memory resources are again limited by the number of training samples, quickly filled by the large‐scale data. El Zini et al 19 applied ELM to recurrent neural network (RNN) training which normally performed with back propagation (BP). GPU acceleration was also integrated to speed‐up the iterative and time consuming BP training.…”
Section: Related Workmentioning
confidence: 99%
“…However, this work is for the batch ELM algorithm and again it does not involve any regularization to prevent over-fitting and memory resources are again limited by the number of training samples, quickly filled by the large-scale data. El Zini et al 19…”
Section: Related Workmentioning
confidence: 99%